2009
DOI: 10.4067/s0716-97602009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Hormesis response of marine and freshwater luminescent bacteria to metal exposure

Abstract: The stimulatory effect of low concentrations of toxic chemicals on organismal metabolism, referred to as hormesis, has been found to be common in the widely used luminescence bioassay. This paper aims to study the hormesis phenomenon in both marine and freshwater luminescent bacteria, named Photobacterium phosphorem and Vibrio qinghaiensis. The effects of Cu (II), Zn (II), Cd (II) and Cr (VI) on luminescence of these two bacteria were studied for 0 to 75 minutes exposure by establishing dose-and time-response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Marine and freshwater luminescent bacteria exposed to metals, showed a clear hormetic phenomenon in luminescence assays (Christofi et al 2002;Shen et al 2009;Deng et al 2012). However, in pathogenic and commensal bacteria the occurrence of hormetic response induced by low doses of antibiotics has not been yet demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Marine and freshwater luminescent bacteria exposed to metals, showed a clear hormetic phenomenon in luminescence assays (Christofi et al 2002;Shen et al 2009;Deng et al 2012). However, in pathogenic and commensal bacteria the occurrence of hormetic response induced by low doses of antibiotics has not been yet demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Samples showing hormesis are currently non-toxic. Hormesis is a widespread phenomenon in the exposure to metals with luminescent bacteria, because the V. fischeri is generally less sensitive to metals than to plant and animal cells [47,48]. In the research by Shen et al [48], a clear hormesis phenomenon was observed in all tested metals (Cu, Zn, Cd, Cr) at a low concentration under the condition of luminescence assay.…”
Section: Vibrio Fischeri Responsementioning
confidence: 99%
“…Hormesis is a widespread phenomenon in the exposure to metals with luminescent bacteria, because the V. fischeri is generally less sensitive to metals than to plant and animal cells [47,48]. In the research by Shen et al [48], a clear hormesis phenomenon was observed in all tested metals (Cu, Zn, Cd, Cr) at a low concentration under the condition of luminescence assay. Luminescence stimulation by exposure to zinc, cadmium, and chromium was also found in research by Christofi et al [43], who showed an enhancement of luminescence induced by low concentrations of these metals.…”
Section: Vibrio Fischeri Responsementioning
confidence: 99%
See 1 more Smart Citation
“…This is called as hormesis that somehow the bacteria's viability gets stronger than the initial state. Shen et al (2009) reported the stimulatory effect of low concentrations of toxic chemicals on organismal metabolism is common in luminescent bioassay (Fulladosa et al, 2005(Fulladosa et al, , 2007. The increased light amount varies at exposure time and dose of toxicant.…”
Section: Hormesismentioning
confidence: 99%